Apollo 15 : in the mountains of the moon (American history in video., 1971)
Covers the Apollo 15 lunar landing mission of July 1971, highlighting the first use of the lunar roving vehicle (LRV). Includes details of the scientific research projects and the dramatic splashdown back on earth with one parachute collapsed.